Effect of Fermentation on Nutrient and Antinutrient Contents of Cocoyam Corm - Adegbehingbe Kehinde Tope; Fakoya Soji (Journal of Pharmacy and Nutrition Sciences, 2013)
Objective: Cocoyam corms were fermented with the aim of enhancing and reducing its nutrient and antinutrient contents respectively. Methods: Cocoyam corm was fermentated naturally by submerged fermentation method in a sterile medium (distilled water) for four days. Microbial examination of the fermenting corms was carried out at 24hours interval for four days. Results: Twenty bacterial strains were isolated within the fermentation periods. They include the general: Micrococcus species, Lactobacillus plantarum, L. fermentum, Enterobacter, Escherichia coli and Staphylococcus aureus. The total bacteria count increased from 5.70 log cfu/ml to 8.97 log cfu/g while fungal count increased from 3.33 log cfu/g to 4.84 log cfu/g. Temperature and the total titratable acidities increased from 27oC to 35oC and 1.13% to 3.72% respectively while the pH values decreased from 5.68 to 3.75. The result of the proximate analysis showed that the fermented sample had higher protein (12.00%), ash (2.84%) and fat (4.84%) contents than the unfermented sample which contained 7.30%, 2.4% and 4.55% respectively. However, moisture, fibre and carbohydrate contents decreased from 9.70%, 3.00% and 73.04% in unfermented sample to 8.94%, 2.78% and 67.60% in fermented sample respectively. All the antinutrient contents decreased at the end of the fermentation [phytate (1.32-0.38) g/100DM, oxalate (0.72-0.21) g/100DM, tannin (0.18-0.07) g/100DM, saponin (0.45-0.22) g/100DM, hydrocyanide (22.27-10.22)g/kg of the fermented sample than the unfermented one.